Le quartier et la tour de l’Europe à Mulhouse (1959-2015). Perspectives européennes d’un patrimoine transfrontalier - Amandine Diener (In Situ)
After a glorious industrial past during the nineteenth century, the city of Mulhouse suffered from the economic changes of the 1930s and had to be rebuilt after the Second World War. Emile Muller (1915-1988), the city’s mayor during the Trente Glorieuses, the post-war period of prosperity, undertook some audacious urban projects such as the conversion of the Dentsche neighbourhood into the Quartier Europe. Designed according to the tenets of the Modern Movement, this urban project, separating pedestrians from traffic by the creation of concrete platforms, had a residential tower block at the heart of its composition, designed by François Spoerry (1912-1999), a Mulhouse architect, working in association with Bernard Michau (1928-). Inaugurated in May 1973, this tower symbolised the coming together of a cross-border territory and generated much debate about architectural styles. Unlike the institutional buildings going up at Strasbourg during the same period, the tower, with its residential programme, embodied the expression of a new cultural and political identity in Europe. It also part of the history of tall buildings in Europe. From archival and published sources, this article looks at the genesis of this project and examines the geopolitical and architectural ambitions which inspired its designers. It looks too at the limitations of the project which, in the context of the general cultural values of the time, failed to win public appreciation. A label given to the twentieth-century heritage, « Patrimoine du xxe siècle » was conferred on the tower in 2015 and may help improve its appropriation by the local population.